Development of rapid lamp assays for the detection of potential nosocomial pathogens / Dong Hong - Dong, Hong (2013)

(untitled)
Nosocomial pathogens are organisms that cause diseases in a patient during his/her stay in a hospital or health care center. These pathogens can spread easily in the hospital and cause an outbreak because of the low immune system of the hospitalized patients. Even so, they are resistant to most of the antibiotics. Rapid detection of these pathogens would be useful to trace the source of an outbreak. In this study, a new detection method, the loop-mediated isothermal amplification (LAMP) was developed for the rapid detection of three nosocomial pathogens which are highly multidrug resistant. They are Acinetobacter baumannii, Pseudomonas aeruginosa and Klebsiella pneumoniae. Acinetobacter baumannii is a Gram-negative bacterium which can cause serious infection. It can cause wound infection, pneumonia, urinary tract infection, and etc. The LAMP primers for Acinetobacter baumannii were based on gltA gene and amplified in 62℃ for 90 min. The assay was evaluated on 50 bacterial strains, including 30 Acinetobacter baumannii and 20 non-Acinetobacter baumannii. All the positive strains were correctly identified, while the negatives were true negative. The sensitivity of LAMP was 5.5×104 CFU/ml, and it was 10-fold more sensitive than the normal PCR method (5.5×105 CFU/ml). The sensitivity of both LAMP and PCR were the same at 5.5×105 CFU/ml in spiked blood samples. Pseudomonas aeruginosa causes pneumonia, otitis, endocarditis, septicemia and keratitis. The LAMP primers for P. aeruginosa were based on 16S rRNA-processing protein rimM gene and amplified at 65℃ for 60 min. The specificity of the primers was also evaluated on 50 strains (30 P. aeruginosa, 20 non-P. aeruginosa). The detection limit of this assay on bacterial culture was 3.6×104 CFU/ml, and it was 1000-fold more sensitive than PCR (3.6×107 CFU/ml). For spiked blood samples, the detection limit for LAMP was 7.7×104 CFU/ml which was 1000 fold higher than PCR (7.7×107 CFU/ml). Klebsiella pneumoniae is a bacterial pathogen which causes pneumonia, bacteremia and meningitis. The LAMP primers were based on ABC transport permease gene and amplified at 65℃ for 90 min. The assay was evaluated on 50 bacterial strains, including 30 Klebsiella pneumoniae and 20 non-Klebsiella pneumoniae. There was no false positive or false negative result. The detection limit of LAMP was 7×103 CFU/ml, which was the same with normal PCR method. For spiked blood samples, the detection limit of both LAMP and PCR was the same at 1.4×104 CFU/ml. Overall, LAMP is a rapid, effective and efficient assay which would contribute to the efficient detection of nosocomial pathogens.